Serious Games: The Challenge ITEC/CIP and T 2011: Joint Conference of the Interdisciplinary Research Group on Technology, Education, and Communication, and the Scientific Network on Critical and Flexible Thinking Ghent, Belgium, October 19-21, 2011, Revised Selected Papers - Wannemacker, Stefan; Vandercruysse, Sylke; Clarebout, Geraldine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the Joint Conference of the Interdisciplinary Research Group on Technology, Education, Communication, and the Scientific Network on Critical and Flexible Thinking, held in Ghent, Belgium, in October 2011. The 12 papers in this volume represent extended versions of the 20 papers presented at the conference and selected from numerous submissions. The conference brought together scholars and researchers who study the use of serious games in educational settings from different perspectives, such as instructional design, domain specific didactics, cognitive and computer science.
instructional design -- domain specific didactics -- cognitive and computer science.
Keywords: Computer science; Artificial intelligence; Education; Computer Science; Personal Computing; Computers and Education; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Computers and Society